2013
DOI: 10.1159/000348517
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Brain and Multivoxel Spectroscopy in Very Low Birth Weight Infants Related to Insulin-Like Growth Factor Concentration and Early Growth

Abstract: Background: Very low birth weight (VLBW) children have higher risk of neurologic disabilities and growth factors are essential for brain maturation. Aim: To assess whether there are differences in neurologic findings, psychometric parameters and microstructural brain morphology in 1-year-old VLBW infants versus term healthy controls and whether these differences are related to hormonal/growth changes. Methods: Prospective anthropometry, prefeed venous blood sample [insulin, insulin-like growth factor-I (IGF-I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In premature infants, a higher rate of increase of IGF I until 35 wk postmenstrual age has directly been related to a better neurodevelopmental outcome at 2 y of age (39). In line with that, Okuma et al found that IGF I levels were associated with white matter organization (42). Interestingly, mean IGF I concentration was positively correlated to neurodevelopmental outcome during a period, from 30 to 35 wk postmenstrual age, when a surge in IGF I levels occurred and infants started growing after a phase of postnatal growth restriction (14,39).…”
Section: The Role Of Igf I In Neurodevelopmentmentioning
confidence: 76%
See 1 more Smart Citation
“…In premature infants, a higher rate of increase of IGF I until 35 wk postmenstrual age has directly been related to a better neurodevelopmental outcome at 2 y of age (39). In line with that, Okuma et al found that IGF I levels were associated with white matter organization (42). Interestingly, mean IGF I concentration was positively correlated to neurodevelopmental outcome during a period, from 30 to 35 wk postmenstrual age, when a surge in IGF I levels occurred and infants started growing after a phase of postnatal growth restriction (14,39).…”
Section: The Role Of Igf I In Neurodevelopmentmentioning
confidence: 76%
“…Nonetheless, Hansen-Pupp et al could not associate protein and caloric intake with brain volumes (39) and in several studies protein-enriched nutrition failed to improve neurodevelopmental outcome up to 18 mo corrected age (53,66,69,70). Macro-and microstructural brain analyses could not be correlated to intake of protein or other nutritional components either (42). Yet, two studies by Stephens et al and Cormack et al showed that protein intake in the first weeks of life was positively correlated with the cognitive and motor score on the Bayley Scales of Infant Development (71,72).…”
Section: The Role Of Dietary Proteins In Neurodevelopmentmentioning
confidence: 98%
“…After the CA at term, the IGF-I concentrations increased independent of birth weight SDS. Higher IGF-I concentrations in early life have been found to be associated with later risks of noncommunicable diseases [26] but are positively associated with brain volume and maturation patterns [2]. In fact, higher IGF-I levels in preterm infants during the first weeks after delivery have shown to be protective against the development of retinal and bronchopulmonary dysplasia with an increase of 5 ng/mL in the mean IGF-I during postmenstrual ages 30–33 weeks, decreasing the risk of proliferative retinopathy of prematurity by 45% [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, the incidence is ≈5–12%, depending on the expertise of the reproductive and maternity unit, but the great majority (> 85%) are born moderately preterm or near term (gestational age < 37 and > 32 weeks), and are usually termed low birth weight (weight below 2,500 g) [1]. Among premature newborns, those with very low birth weight (VLBW) (weight below 1,500 g and/or gestational age below 32 weeks) present an additional challenge due to their increased risk of sequelae and long-term disabilities, which have been inversely associated with early postnatal growth and circulating growth factors [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies also show that IGF-1 levels correlate with brain volumes while no association with cerebral spinal fluid volume was observed. Others found an association of IGF-1 levels with white matter organization and that low birth weight infants had smaller brain volume in general[133]. Higher systemic IGF-1 levels are related to better outcome in terms of neurodevelopment at age 2[134].…”
Section: Introductionmentioning
confidence: 99%